Sifat Kimia Kayu Jati (Tectona grandis) dengan Busuk Hati - , MUKHLIS ARDIANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Teak wood is considered as a superior timber in Java. However, it could not be ascertained that the best condition is be produced every time. Even the wood looks sound from the outside, it isnot necessarily a sound wood inside, as a case of heart-rot wood. Nowadays, it still remains unknown of the cause of such abnormality. This study aimed to determine the differences in the chemical properties of the solid parts and decayed inner heartwood to analize the different variation in the intensity of heart-rot attacked wood, as well as to compare the tendency of the chemical properties in the radial position between the heart-rot affected and normal woods. The materials used of this study for intra-tree variation were from Gunungkidul Region. It consisted of one heart-rot affected tree which the samples were then divided axially (the base, middle, and top). In addition, a normal tree for comparison was also cut. The materials used for between-tree variation were felled from KPH Randublatung, Perum Perhutani. It comprised of 3 heart-rot affected trees and a normal tree for comparison. The samples of heartrot wood observed were solid parts (sapwood, outer hearwood, inner heartwood) and the decayed inner heartwood. From each section, the samples were sized into 40-60 mesh powder for testing the chemical properties of wood. Chemical properties tested were holloselulose, alfa-cellulose, lignin, ethanol-toluene extractive, hot water extractive, solubility in NaOH 1%, and ash contents, as well as thepH value. The data analysis used in this study was descriptive statistic. The solid heartwood affected by heart-rot showed the increasing in the hot water extractive content level. Further, the difference tendency was more observed in the cell wall components with regard to intra-tree variation. Decayed inner heartwood,which is affected by heart-rot, had a decreasing level of alphacellulose content while those increasing level in lignin, solubility in 1 % NaOH, hot water extractives, and ash contents was found. Based on these data, the caused of heart-rot was indicated by the brown-rot. Teakwood affected by heart-rot with a bigger diameter showed a decreasing in alphaâcellulose content while the level of lignin, solubility in 1 % NaOH, hot water extractive, and ash contents, also the pH values increased. Those differences were more visible in the betweenâtree variation. The different tendencies in the chemical properties in radial direction were more noticed especially in sapwood-heartwood and inner heartwood-outer heartwood of affected heart-rot and normal wood. This is due to the distribution of the chemical components of the cell wall. Keywords : Tectona grandis, heart-rot, chemical properties, decay, radial direction 1) College Student, Departement of Forest Product Technology, Forestry Faculty, UGM 2) Lecture, Departement of Forest Product Technology, Forestry Faculty, UGM